Reconstruction of Inheritance Dispute Resolution in Religious Court Decisions in Indonesia - Muhammad Farhan Fardiansyah; Ikhwanuddin Abdul Majid; Fawaz Diya’a Rabbi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Inheritance disputes constitute a significant proportion of civil cases adjudicated in Indonesian courts, particularly within the jurisdiction of the Religious Courts applying Islamic inheritance law. Conflicts frequently arise over the determination of rightful heirs, the calculation of distributive shares, and the management of inherited property. Such disputes are often rooted in dissatisfaction among heirs, competing claims of entitlement, and differing interpretations of legal and religious norms. The Islamic inheritance system, including the well-known 2:1 ratio between male and female heirs in certain categories, is sometimes perceived as inequitable, thereby intensifying familial tensions and litigation. This study aims to identify the dominant types of inheritance disputes brought before Indonesian courts and to analyze the judicial reasoning and legal methodologies employed in resolving them. Using a qualitative normative-empirical approach, the research examines court decisions, statutory regulations, and doctrinal interpretations to explore how judges reconcile classical Islamic inheritance principles with contemporary notions of justice and social harmony. The findings indicate that judges adopt various interpretative strategies, including systematic statutory interpretation, contextual reasoning, and mediation-oriented approaches, to ensure equitable and socially acceptable outcomes. By mapping the patterns of disputes and judicial considerations, this article contributes to a deeper understanding of the practical implementation of Islamic inheritance law in Indonesia and offers insights for improving consistency, fairness, and dispute resolution mechanisms in future inheritance cases.